COVID-19 AND PREGNANCY-OUR EXPERIENCES - Cvetanovska, Marija; Demiri, Ilir; Grozdanovski, Krsto; Spasovska, Katerina; Daneva- Markova, Ana; Stojanoska, Tatjana; Cvetanovski, Vlatko (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
A retrospective analysis was made on 35 patients: 25 pregnant women and 10women in the early postpartum period with clinical and laboratory confirmed COVID 19. On admission demographic, clinical, lab parameters, comorbidities, complications and parameters correlated with the pregnancy and the mode of delivery were observed. Sars Cov 2 was confirmed in a nasopharyngeal swab with a molecular method of RT-PCR. The average age was 30.7 years old. 21(84%) were in their third trimester and 16 (45.7%) had comorbidities. The most common complication was pneumonia 31 (88.57%) and the most frequent symptoms were: fever 26 (74.2%), cough 25 (71.4%), malaise 19 (54.28%) and dyspnea 15 (42.85%). 20 (57.4%) patients displayed severe clinical condition with need of oxygen support and they were all treated in the  intensive care unit. 3 (15% ) were placed on non-invasive ventilation, and 4 (20%) needed mechanical ventilation, all of them in the postpartum period. Mortality rate was 3 (8.57%) and it was registered only in the postpartum period.Covid 19 in pregnancy and among the general population shares the same clinical manifestations. Pregnant women having pneumonia, more than one comorbidity, are in the third trimester of their pregnancy or in their postpartum period, were pointed out as having the highest risk of getting severe clinical condition and a poor outcome. In the light of the above, these are the patients in need of intensive observation and monitoring, as well asnecessary, strict anti-epidemic measures and prioritized vaccination. Key words : Covid 19, pregnancy. https://doi.org/10.55302/JMS2143131c